(untitled) (Acta Scientiarum. Agronomy, 2017)
This study aimed to evaluate the structural changes and reserve deposition of malagueta and biquinho pepper seeds and to determine their chemical composition during ontogeny. The fruits were collected 25, 40, 55, 70, 85, and 100 days after anthesis (DAA). After collection, the seeds were extracted and fixed in FAA 50 and then stored in 70% ethanol. Subsequently, the seeds were embedded in methacrylate (Historesin) and sectioned with a microtome. The sections were stained with Toluidine blue O for anatomical analysis and Xylidine Ponceau, Periodic acid Schiff (PAS) and Lugol’s iodine solution for histochemical analysis. Sections were made using a cryomicrotome for acid phloroglucinol staining and Sudan III tests. Progressive lignification of the seed coat cells was observed. Proteins and lipids were the main reserve compounds of malagueta and biquinho pepper seeds stored in the embryo and endosperm. Starch served as a transient reserve during embryo development. The lipid reserves were observed in embryo and endosperm cells from 25 until 100 DAA. At 100 DAA, the protein contents of the malagueta and biquinho pepper seeds were 0.33 and 0.62 g g-1 DM and the lipid contents were 0.30 and 0.25 g g-1 DM, respectively.